Concentrations of organic and inorganic indicators in bulk sediments from Bilanko peat core in the Batéké Plateaux, Republic of the Congo - Henrique Gloire Lungela Tchimpa; Suspense A Ifo; Hilaire Elenga; Laure Gandois; Brice Milongo; Martine Marie Bernadia Wando; Divine Okiemba Atipo; Yannick Garcin (PANGAEA, 2025)
This publication contains data from an organic and inorganic geochemistry database of one of three peat cores taken from three peatlands: two in the Batéké Plateaux (Ngamakala and Bilanko – this dataset), and one in the central Congo Basin (Ossangou), all of which are located in the Republic of the Congo. The aim in generating these data was to obtain information on the formation and evolution of these peatlands and their implications for the region extquotesingles paleoenvironment and paleoclimate. The peat cores were collected using a 50 cm long stainless steel Eijkelkamp Russian-type corer during a field campaign from June to July 2022. Each core was split into 10 cm samples, on which all analyses were performed in 2023 and 2024. Radiocarbon dating was performed using the Accelerated Mass Spectrometry (AMS) at the ARTEMIS facility on LMC14 National Laboratory, France, and the MICADAS AMS at the EchoMICADAS facility on Laboratoire des Sciences du Climat et de l extquotesingleEnvironnement (LSCE) in Gif-sur-Yvette, France. The obtained ages were calibrated using a 50:50 mixed calibration curve between the Northern Hemisphere curve (IntCal20, Reimer et al., 2020) and the Southern Hemisphere curve (SHCal20, Hogg et al., 2020). Organic elemental and isotopic geochemistry was performed using a Delta Plus XP EA-IRMS mass spectrometry analyser (ThermoFinnigan), coupled to an EA 1112 Flash elemental analyser. Inorganic geochemical data were obtained by inductively coupled plasma mass spectrometry (ICP-MS, PerkinElmer NexION 300X, USA) and inductively coupled plasma optical emission spectrometry (ICP-OES, Agilent 5800 VDV).